Public Administration Ecology: Environmental Integration Into Policy - Muhamad Ilham (GoResearch - Research & Publishing House, 2024)
This research aims to explore the integration of ecology in public policy. There is often a conflict between short- term economic interests and long-term environmental protection goals. Governments and other stakeholders often prioritize economic growth over ecological sustainability. In this study, the method used is qualitative. qualitative research method is a study used to research on natural objects where the researcher is the key instrument, data collection techniques are combined, data analysis is inductive, and qualitative research results emphasize meaning rather than generalization. This article emphasizes the importance of ecological integration into public policy, not only for environmental preservation but also for social and economic benefits. Specific examples mentioned include sustainable agricultural practices and ethical water management policies, which can improve people's well-being and food security. Environmental challenges faced by governments, such as pollution, deforestation and climate change, require a holistic and science-based policy approach. Public policies that consider ecological principles can ensure that economic and social development go hand in hand with environmental conservation.